Realization of BaZrS3 chalcogenide perovskite thin films for optoelectronics. (February 2020) - Wei, Xiucheng; Hui, Haolei; Zhao, Chuan; Deng, Chenhua; Han, Mengjiao; Yu, Zhonghai; Sheng, Aaron; Roy, Pinku; Chen, Aiping; Lin, Junhao; Watson, David F.; Sun, Yi-Yang; et al.
Abstract: BaZrS3 is a prototypical chalcogenide perovskite, an emerging class of unconventional semiconductor. Recent results on powder samples reveal that it is a material with a direct band gap of 1.7–1.8 eV, a very strong light-matter interaction, and a high chemical stability. Due to the lack of quality thin films, however, many fundamental properties of chalcogenide perovskites remain unknown, hindering their applications in optoelectronics. Here we report the fabrication of BaZrS3 thin films, by sulfurization of oxide films deposited by pulsed laser deposition. We show that these films are n-type with carrier densities in the range of 10 19 -10 20 cm −3 . Depending on the processing temperature, the Hall mobility ranges from 2.1 to 13.7 cm 2 /Vs. The absorption coefficient is > 10 5 cm −1 at photon energy >1.97 eV. Temperature dependent conductivity measurements suggest shallow donor levels. By assuring that BaZrS3 is a promising candidate, these results potentially unleash the family of chalcogenide perovskites for optoelectronics such as photodetectors, photovoltaics, and light emitting diodes. Graphical abstract: Image 1 Highlights: The first fabrication of high quality chalcogenide perovskite BaZrS3 thin films, opening the door for device applications. Exceptionally high absorption coefficient higher than 10 5 cm -1 at photon energy greater than 1.97 eV. n-type doping with carrier mobility greater than 10 cm 2 /Vs. Shallow defect level.